Target groups for organic wine: The importance of segmentation analysis. (January 2020) - Janssen, Meike; Schäufele, Isabel; Zander, Katrin
Highlights: Organic not the most important wine attribute for most organic food consumers. Different segments have partly opposite preference structures for price and origin. Growth potential for organic wine identified. Comparison of two analysis methods for choice data provides interesting insights. Abstract: In light of low and stagnating market shares of organic wine, there is an ongoing debate about growth potential for organic wine. A recent study revealed that even consumers of organic food did not necessarily purchase organic wine regularly. The aim of this contribution was to analyse the wine preferences of organic food consumers and identify promising new target groups for organic wine. We conducted choice experiments in Germany (N = 600) and analysed the data with mixed logit models and latent class models, revealing interesting differences between the results of the two approaches. While the mixed logit models suggested 'organic' was the most important wine attribute, the latent class models challenged this proposition. While three of four consumer segments had a strong preference for organic, only one segment in the red wine model (and no segment in the white wine model) gave organic highest priority. Just like non-organic consumers, many organic food consumers seem to use price or country of origin as the most important quality cue for wine. The comparison between the results of the choice experiments and the participants' stated normal purchase behaviour suggested there is growth potential for organic wine. Apparently, consumers of organic food would buy more organic wine if their preferred type and variety of conventional wine would be available in organic quality at similar price levels.